PELATIHAN PENGGUNAAN BIRTH BALL SERTA ESSESIAL OIL PADA BIDAN DAN KADER DI PUSKESMAS NGESREP - Tia Nurhanifah; Desi Soraya; Anifatus Sa'adah (P3M Universitas Aisyiyah Surakarta, 2026)
The birth process is a physiological event that is inherently associated with pain. Labor pain must be managed effectively because, when accompanied by stress responses, it can have harmful effects on both the mother and fetus. Pain during childbirth can be managed through pharmacological and non-pharmacological approaches. The identified problem in the community is the suboptimal use of birth balls and essential oils as non-pharmacological methods to reduce pain and promote relaxation during labor. This community service activity aimed to empower midwives and health cadres in utilizing birth balls and essential oils through a peer group discussion method. Several midwives and cader were trained in the basic techniques of using birth balls, applying essential oils, and preparing simple essential oil blends. The activity was conducted at the Ngesrep Primary Health Center. The results showed that midwives and cader were able to provide education on the use of birth balls and essential oils to support successful and minimally traumatic childbirth. As a follow-up, cader are expected to serve as key motivators in promoting the use of birth balls and aromatherapy within the community. Public support is also encouraged to enhance the adoption of these methods to improve childbirth outcomes with minimal trauma.